Income inequality and price elasticity of market demand: the case of crossing Lorenz curves - Ibragimov,M; Ibragimov,R; Kattuman,P; Ma,J (Economic Theory, 2018)
This paper extends Ibragimov and Ibragimov (Econ Theory 32:579–587,2007) in which the effect of changes income inequality on the price elasticity ofmarket demand is characterized for the class of income distribution changes occurringthrough non-intersecting Lorenz curve shifts. We derive sufficient conditionsfor increase/decrease in price elasticity of market demand, under general changes inincome distribution, allowing Lorenz curves to intersect as they shift. We conclude bydrawing out implications of different types of tax policy changes for demand elasticity.